A Calculation of Percent Disability in Occupational Injury Cases a Forensic Assessment - Birgen, Nur; Okudan, Mustafa; Okyay, Mesut; İnanıcı, Mehmet Akif (The Bulletin of Legal Medicine, 1999)
Over the years there has been numerous problems both in the assessment and percent calculation of disability in Turkey. It seems that the problem of assessment arise from incomplete or wrong determination of malfunction of the injured area. It is therefore essential that forensic examiners follow a method of calculation that is fair both to the victim and employer. The purpose of this study is to present an epidemiology of personal injury leading to disability and illustrate how a percent, age is calculated correctly. The sample is composed of all individuals with occupational injuries who were examined to determine individual percent disability by the Third Specialization Board of the Council of Forensic Medicine during 1994 to 1998. There werel39 people. 135 of them were males, 4 were females. Results indicate that the age group with the greatest number of trauma was in 29-33 years. The most common injury was in the pelvis and lower extremity (31%) and a loss of orthopedic function (e.g., shortening of a leg) was seen in 45% of the group. Of the total percent disability, the highest frequency was in the 10-25% group (32%). Comparatively, the present study shows a number of similarities to previous studies in terms of sex distribution, anatomic location and percentage of injuries. While there are epidemiological similarities, the percent disability calculation presented in the study is a technique that seems to provide the best result that can be employed by other forensic experts. Key words: Disability, Determination of disability, Occupational injury.